How to reduce the impact of contaminated seafood on public health with the discharge of Fukushima nuclear wastewater - Bai, Yuntao; Yuan, Xiaolong; Wang, Lan (Frontiers in Sustainable Food Systems, 2023)
As wastewater from the Fukushima nuclear disaster continues to drain into the sea, the supply system for healthy seafood is being seriously challenged. To protect public health, it is necessary to restructure the seafood supply mode. The seafood supply mode is divided into the original mode, land farming mode, and strengthen monitoring mode. To derive the applicable scope of the various modes of the seafood supply chain and to provide recommendations for the safety and sustainability of seafood supply chains for governments and enterprises, three differential game models are constructed in this study. Then, the equilibrium results obtained by the models are compared and analyzed. Based on the findings, the health impact of seafood pollution is relatively small, and the government tends to choose the original supply mode. As the health impact of seafood grows, governments tend to prefer land-based farming. The social benefit to the government is directly proportional to the monitoring cost of seafood. To protect public health, enterprises tend to choose the mode of strengthen monitoring if the proportion of unqualified seafood is low. In addition, if sea products show a high degree of adaptation to the land environment, they tend to choose land farming.